Holey nickel hydroxide nanosheets for wearable solid-state fiber-supercapacitors. Issue 12 (12th March 2018) - Shi, Peipei; Chen, Rong; Li, Li; An, Jianing; Hua, Li; Zhou, Jinyuan; Liu, Bin; Chen, Peng; Huang, Wei; Sun, Gengzhi
Abstract : Ultrathin and holey nickel hydroxide nanosheets are synthesized and embedded in carbon nanotube fiber for high performance wearable supercapacitors. Abstract : Holey nickel hydroxide (Ni(OH)2 ) nanosheets with a mean thickness of 2 nm are facilely synthesized, and then embedded in carbon nanotube (CNT) scaffolds to construct a hybrid fiber electrode, which shows a high volumetric capacitance of 335.9 F cm −3 at 0.8 A cm −3 and superior rate performance. The hybrid supercapacitor made from the Ni(OH)2 /CNT fiber can deliver a high specific capacitance of 24.8 F cm −3 and an energy density of 5.8 mW h cm −3 with outstanding mechanical stability under repeated bending conditions.